Investigating the conformity between the Zimbabwe land administration system and the Land Administration Domain Model - Mtariswa, Tinashe (Midlands State University, 2017)
The increase in land utilization has necessitated the devising of more adequate technologies for better management and administration of the nation’s most valuable resource. The land administration functions in Zimbabwe are distributed within several departments. This has necessitated the need for effective communication between the departments to ensure effective service delivery. The need for a National Land Information System in Zimbabwe has coincided with the development of the Land Administration Domain Model (LADM). The main goal of the LADM is to improve communication between Land Administration systems locally, regionally and internationally. LADM can be a basis for combining data from different Land Administration systems, for example systems with datasets on formal and informal people-to-land relationships. The main aim of this study is to investigate the conformity between the Zimbabwe land administration system and the LADM. The first stage in the investigation is to analyze the current land administration system in Zimbabwe. The analysis results are then used to define the current land administration model in Zimbabwe. The model is then compared with the land administration domain model to determine difference and similarities between the models. The comparison is also a basis for determining the LADM packages that can be directly implemented in the Zimbabwe land administration system, the packages that will not be required and the packages that might need to be modified. In this research project the conceptual models of all the party packages were developed using Unified Modeling Language (UML).